QUIC Transport and Dispersion Modeling of Vehicle Emissions in Cities for Better Public Health Assessments - Michael J. Brown; Michael D. Williams; Matthew A. Nelson; Kenneth A. Werley (SAGE Publishing, 2015)
The Quick Urban and Industrial Complex (QUIC) plume modeling system is used to explore how the transport and dispersion of vehicle emissions in cities are impacted by the presence of buildings. Using downtown Philadelphia as a test case, notional vehicle emissions of gases and particles are specified as line source releases on a subset of the east-west and north-south streets. Cases were run in flat terrain and with 3D buildings present in order to show the differences in the model-computed outdoor concentration fields with and without buildings present. The QUIC calculations show that buildings result in regions with much higher concentrations and other areas with much lower concentrations when compared to the flat-earth case. On the roads with vehicle emissions, street-level concentrations were up to a factor of 10 higher when buildings were on either side of the street as compared to the flat-earth case due to trapping of pollutants between buildings. However, on roads without vehicle emissions and in other open areas, the concentrations were up to a factor of 100 times smaller as compared to the flat earth case because of vertical mixing of the vehicle emissions to building height in the cavity circulation that develops on the downwind side of unsheltered buildings. QUIC was also used to calculate infiltration of the contaminant into the buildings. Indoor concentration levels were found to be much lower than outdoor concentrations because of deposition onto indoor surfaces and particulate capture for buildings with filtration systems. Large differences in indoor concentrations from building to building resulted from differences in leakiness, air handling unit volume exchange rates, and filter type and for naturally ventilated buildings, whether or not the building was sheltered from the prevailing wind by a building immediately upwind.